Sequence analysis of the complete gene for endoglucanase from strains of thermotolerant bacillus - Pardilla, Kalle P.; Hedreyda, Cynthia T. (2021)
"Three thermotolerant Bacillus isolates from the Philippines-identified as Bacillus subtilis (1280), Bacillus velezensis (1573), and Bacillus amyloliquefaciens (10105)-exhibited cellulase activity in carboxymethylcellulose (CMC) agar plate. Moreover, the expected size (approximately 1,500 bp) putative endoglucanase gene was amplified from all three local isolates. The endoglucanase gene amplified from a Bacillus licheniformis isolate (1320) was also used in the gene sequence analysis"-title page.
Includes bibliographical references.
Keywords: Bacillus (Bacteria).; Cellulase